FREQUENCY AND PREDICTORS OF RENAL ARTERY STENOSIS IN PATIENTS WITH CORONARY ARTERY DISEASE - Shah, S. Sadiq; Noor, Lubna; Sawar, Shah; Awan, Zahid Aslam; Hafeezullah, Muhammad; Khan, Sher Bahadar (Journal of Ayub Medical College Abbottabad, 2010)
Background: Renal artery stenosis (RAS) is a common finding in patients undergoing coronary angiography. We designed this study to look for the frequency and any predictors of renal artery stenosis in patients with coronary artery disease (CAD). Methods: A total of 201 consecutive patients with CAD confirmed by coronary angiography underwent an abdominal aortogram in the same sitting to screen for RAS. Patient demographics and co-morbidities were analysed for any association with RAS. Results: Forty-one of the patients were female (20.4%); ninety patients were hypertensive (44.8%); 49 patients (24.4%) were smokers; 19 patients (9.5%) had renal insufficiency; 88 patients (43.8%) had high cholesterol levels; 44 patients (21.9%) were diabetic. Thirty-two patients (15.9%) had single coronary artery disease, 59 patients (29.4%) had two vessel disease, and 110 patients (54.7%) had three vessel disease. Significant renal artery stenosis (ï‚³50% stenosis) was present in 26 patients (12.9%). Among the variables studied, only female gender was found to be associated with a higher frequency of renal artery stenosis (24.39% vs 10.0%, p=0.01). Conclusions: The frequency of renal artery stenosis in patients with coronary artery disease is 12.9%. Female gender is associated with a higher frequency of renal artery stenosis in patients with CAD. Keywords: Renal Artery Stenosis, Coronary Artery Disease, Atherosclerosis